2010 Proceedings of the 56th IEEE Holm Conference on Electrical Contacts 2010
DOI: 10.1109/holm.2010.5619524
|View full text |Cite
|
Sign up to set email alerts
|

Contact Resistance Characteristics of Relay Operated in the Vicinity of Silicone-Type and Non-Silicone-Type Polymeric Cured Materials at Elevated Temperatures

Abstract: Influences of vapors evaporated from a newlydeveloped acryl-based polymeric material (containing no silicone components) and conventional silicone-containing polymeric materials were evaluated with respect to their effects on contact resistance characteristics of relay contacts at an ambient temperature of 120ºC. More specifically, a commerciallyavailable mechanical relay (AgSnIn contacts) was sealed into a can with one of the two materials, and placed in a heating chamber to operate, at an operating frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The authors have been already reported some experimental results on influences of this acryl-based non-silicone-type polymeric material on contact resistance characteristics of a mechanical relay in comparison with those with conventional silicone-containing polymeric materials at elevated ambient temperatures of, such as, 80ºC and 120ºC [9][10][11][12][13]. In this paper, results obtained up to now, including previously reported data, are summarized in order to demonstrate advantages of the acryl-based non-silicone-type polymeric material over the conventional silicone-containing materials.…”
Section: Introductionmentioning
confidence: 99%
“…The authors have been already reported some experimental results on influences of this acryl-based non-silicone-type polymeric material on contact resistance characteristics of a mechanical relay in comparison with those with conventional silicone-containing polymeric materials at elevated ambient temperatures of, such as, 80ºC and 120ºC [9][10][11][12][13]. In this paper, results obtained up to now, including previously reported data, are summarized in order to demonstrate advantages of the acryl-based non-silicone-type polymeric material over the conventional silicone-containing materials.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of Silicone in the contact area has therefore to be prevented in general. Different approaches for this goal are: complete removal of silicone materials from manufacturing of the switchgear throughout the product life within the application [18]; use of adequate silicone replacements [22][23][24]; or testing and approval of each silicone material in respect of its content of volatile Silicone and contact compatibility [4]. The aim of this work is to study the capability of relay housings to act as Silicone barriers: Relays with plastic housings with different sealing ratings were put into Silicone environments.…”
Section: Introductionmentioning
confidence: 99%